Diversity Of Weeds Species Around Mango Tree (Mangifera indica L.) On Critical Land In Jombang Regency - Ma'rifatul Khomsah; Zulfikar Zulfikar (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
Weeds are unwanted wild plants because they can interfere with the main crop cultivation. This study aims to identify and analyze the diversity of weed vegetation that grows around mango trees. This study uses the quadratic method with diagonal observation points and direct exploration techniques. Observation parameters include the type of weed and its population. Then the results of the observations were analyzed using the formula of Important Value Index (INP), Summed Dominance Ratio (SDR), Diversity Index (H'), Index of Similarity (IS), and Dominance Index (C). After doing the research, found 24 species of weeds consisting of broadleaf weeds, puzzles and grasses. The highest SDR value in Tondowulan Village was Cynodon dactylon L. at 13.82%, while in Darurejo Village it was Oplismenus hirtellus (L.) P. Beauv. by 26.53%. Weed diversity was classified as moderate because the weed diversity index value in Darurejo Village was 1.92% while in Tondowulan Village it was 2.31%. The two research locations did not have the same composition of weeds because the similarity value was only 33.33%. There is no weed species that dominates the mango garden because the index value of the weed dominance in Tondowulan and Darurejo Villages in the order of the 3rd largest is less than one.